KEBANGKITAN ISLAM DI INDONESIA (Tela'ah Tentang Munculnya Ormas Islam Awal Abad 20 M) - Abd. Ghofur (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2012)
This writing tries to emphasize critical study aboutgrowing and its organisational amends Islamic at Indonesia, particularly on observation about arouses it Islam people at early century 20 M . Islam has role important to advance people since Islam concerned by its past trip that bright until that past regard moslem clan thinking now Reputed islam as the one only of force alternativing to fix people condition that experiencing downfall that time at various cormtry cleft, including Indonesia. That setback because of West colonization factor and also conditional of internal Islamic people that be over against with problem’s sort